SUSTAINABLE PRACTICES IN HOSPITALITY AS A TOOL FOR THE DEVELOPMENT OF ECOLOGICAL TOURISM - Marusei, Tetiana (Current Problems of Sustainable Development, 2026)
The article examines sustainable practices in the hospitality sector as a tool for developing eco-tourism. Key aspects of environmental standards in the hotel business are identified. An analysis of the geographical distribution of certified hotels in Ukraine and their affiliation with international hotel chains is conducted, which made it possible to assess the level of implementation of sustainable development practices in the domestic hotel sector. It is determined that environmental certification is gaining popularity both among international operators and among Ukrainian hotels. The highest level of implementation of environmental standards is observed in regions focused on nature-recreational tourism, which confirms the important role of sustainable practices in the development of eco-tourism and increasing the competitiveness of accommodation establishments. The Ukrainian environmental labeling system “Green Crane” is considered, which is used to designate products and services that meet environmental requirements and have a reduced negative impact on the environment. In the field of hotel services, “Green Crane” can be used as a voluntary environmental benchmark for accommodation establishments that implement environmental practices. A comparison of the Green Crane eco-labeling system and the international Green Key certification was made. In international practice, environmental standards are an integral part of the business strategy of hotels and often determine their market position. They are based on clear regulatory requirements, regular audits and international certification. In Ukraine, environmental initiatives are mostly voluntary and implemented by individual enterprises. The organization of the activities of eco-hotels, which are a promising model for the development of the hospitality sector and one of the effective tools for supporting eco-tourism, is determined. The main purpose of its operation is to ensure a comfortable stay for guests with minimal impact on the environment. The hotel’s environmental performance indicators are proposed.